A Study on Attitude of Urban and Rural College Student Teachers Towards Science - Swarali Sanjay Shah (Universitas Pendidikan Indonesia (UPI), 2022)
Integration of Information, Communication, and Technology (ICT) assist teachers in meeting the global demand for technology-based teaching and learning tools and facilities to replace traditional teaching techniques. ICT is seen as one of the most important factors in the country's future development. The purpose of this study is to examine teachers' perspectives of the effectiveness of integrating ICT into the teaching and learning process in the classroom. A total of 101 instructors from ten public secondary schools in Kuala Lumpur, Malaysia, received a survey questionnaire at random. Using SPSS (version 21) software, the data for this quantitative study was analyzed for descriptive and inferential statistics. The findings show that ICT integration is quite effective for both teachers and pupils. According to the findings, one of the most important variables in the effectiveness of technology-based teaching and learning is instructors' well-equipped preparation with ICT tools and facilities. Teachers' professional development training programs were also found to play an important influence in improving students' learning quality. Other facets of ICT integration, particularly from a management perspective in terms of strategic planning and policymaking, should be considered in future studies.